SDGs and Sustainability Reporting: Their Effect on Financial Performance of Energy Firms in Indonesia - Yazid, Ahmad Haidar; Maryani, Neni (Journal of International Accounting, Taxation and Information Systems, 2025)
The growing global emphasis on sustainability has urged companies, particularly in the energy sector, to adopt sustainable practices and disclose non-financial information such as Sustainable Development Goals (SDGs) and Sustainability Reporting. However, previous studies show inconsistent findings regarding the impact of such disclosures on financial performance, indicating a research gap especially within the Indonesian energy sector, which is central to the transition toward a low-carbon economy. This research examines how SDGs and Sustainability Reporting disclosure affect the financial performance of energy sector companies on the Indonesia Stock Exchange (IDX) from 2019–2023. SDGs are evaluated through the SDGs Index utilizing the 17 global objectives, whereas Sustainability Reporting disclosure is measured via the Sustainability Reporting Disclosure Index (SRDI) based on GRI standards. Financial performance is represented by the Return on Assets (ROA) ratio. The study applies quantitative methodology with descriptive and verificative approaches, utilizing multiple linear regression analysis, classical assumption testing, and individual (t-test) as well as combined (F-test) hypothesis testing. Findings reveal that SDGs show no significant individual impact on financial performance, whereas Sustainability Reporting disclosure demonstrates a significant effect. Simultaneously, both variables affect financial performance. These findings suggest that enhanced sustainability disclosure can improve transparency and stakeholder trust, which may contribute positively to financial performance.